2014
DOI: 10.1002/rcm.7053
|View full text |Cite
|
Sign up to set email alerts
|

A novel high‐temperature combustion based system for stable isotope analysis of dissolved organic carbon in aqueous samples. II: optimization and assessment of analytical performance

Abstract: TOC/IRMS enables fast and reliable measurement of DOC concentrations and δ(13)C values in aqueous samples, without pre-concentration and freeze-drying. Further investigations should focus on complex, saline matrices and very low DOC concentrations, to achieve a potential lower limit of 0.2 mgC/L. Thus, TOC/IRMS will give DOC research in terrestrial and aquatic environments a huge impulse with high-resolution, routine δ(13)C analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…The TOC instrument uses a common high-temperature catalytic combustion method (Kirkels et al, 2014). The analytical method is fully described in Kim et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…The TOC instrument uses a common high-temperature catalytic combustion method (Kirkels et al, 2014). The analytical method is fully described in Kim et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…One interlaboratory comparison study has confirmed a significant discrepancy in the results obtained for the same samples analyzed using different instruments, laboratory protocols, and normalization procedures . Several laboratories still use the δ 13 C values of high‐pressure CO 2 gas cylinders for normalization of measured δ 13 C values to the VPDB scale, e.g . Normalization to the value of the gas reference is the simplest and easiest method to apply; however, in light of the findings of Paul et al and Skrzypek, it also leads to the lowest accuracy among all known normalization methods and should be considered as inappropriate.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] At present, these types of analyses are usually performed using continuous-flow systems employing a wet chemical oxidation (WCO) technique combined with isotope ratio mass spectrometry (IRMS). These WCO-IRMS systems can be total organic carbon (TOC) analyzers [9][10][11] or instruments that couple high-performance liquid chromatography (HPLC) with IRMS. 12,13 The concept of combining HPLC with IRMS was introduced by Thermo Fisher Scientific, and their LC-IsoLink system (Thermo Fisher Scientific, Bremen, Germany) has been available commercially since 2004 and is designed for the stable carbon isotope analysis of a broad spectrum of non-volatile compounds dissolved in water.…”
Section: Introductionmentioning
confidence: 99%
“…3B). However, marine phytoplankton and dissolved organic matter, which can be a major source for bacteria respiration (Maher and Eyre, 2010), tend to have lower values between À20& and 24& (Goericke et al, 1994;Kirkels et al, 2014). In contrast, CaCO 3 dissolution should contribute heavier carbon with d 13 C = À2& (Grottoli, 2000;McConnaughey, 2003).…”
Section: Sources Of Dic and Diel Variation In D 13 C Dicmentioning
confidence: 94%